Pemberdayaan Kelompok Petani Singkong Melalui Pemanfaatan Pangan Lokal di Desa Panaikang Kabupaten Gowa - Nani Apriani Natsir Djide; Novi Puspita Sari; Reski Pebriani (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Indonesia's food security program is one of the most important programs related to population growth in Indonesia and is expected to provide communities with adequate food in both quantity and quality. Foods that need to be covered include local staples, carbohydrate sources, or calorie sources. Cassava is a food source of carbohydrates and horticultural crops and is easily damaged by improper handling.The low price of cassava at the farm level results in losses. Therefore, there is a need for technology that can process cassava into products with higher economic value than raw cassava. Mocha flour making activity was held in Panaykan Village, Gowa District in December 2022 with a total of 24 participants from local farmer groups. This activity begins with a consultation, followed by a training session on how to make mocha flour. Optimizing the use of cassava as a mocha flour is expected to bring greater retail value, improving both economic income and public health.